Transfigurações do passado em narrativas de Teolinda Gersão e Mia Couto - Costa, Daniela Aparecida da [UNESP] (2015)
This study focuses on interactions between literature and history in narratives of two contemporary writers of Portuguese literature: Teolinda Gersão (Portugal) and Mia Couto (Mozambique). To analyze these interactions, four novels were chosen: Gersão's Paisagem com mulher e mar ao fundo, 1982, and A árvore das palavras, 1997; Couto's Terra sonâmbula, 1992, and Vinte e zinco, 1999. By examining how the process of 'transfiguration of the past' works in the chosen narratives, this research confronts different views about revisiting the recent history of Portugal, as the Salazar dictatorship, colonialism, the Colonial War, and the Carnation Revolution - issues linked to both Portuguese and Mozambican identities by the novels in question. In addition to investigating how this process involves the artistic construction of these works, this study aims at presenting how both authors incorporate and appropriate historical facts as narrative strategies. These authors convey unique literary achievements that reveal historical wounds and problematize processes of identity (re)construction. As a result, these literary texts break down barriers between the historical and the fictional, providing us critical reviews of the past both in Portugal and in former Portuguese colonies in Africa, especially Mozambique. The following five groups of theoretical texts support the development of this research: a) theory on the interaction between literature and history, and on the problem of the representation of reality in literary criticism; b) theory on Cultural Studies, for understanding the configuration of literature in newly independent countries, as is the case of Mozambique; c) theory and criticism on the establishment and main trends of Portuguese literature - in particular the production of Mozambique with Mia Couto and of Portugal after the Carnation Revolution, with the work of Teolinda Gersão -, in addition to critical texts on the...